Spectrophotometric determination of xylometazoline in nasal drops - А. О. Donchenko; N. O. Nagorna; S. O. Vasyuk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2018)
Objective. Spectrophotometry is one of the most widely used methods in the pharmaceutical analysis, both for the identification and for the assay of drugs. The main advantages of the method are the relative simplicity of the experiment, high sensitivity, specificity and efficiency. Therefore, the objective of the present work was development of spectrophotometric method for the assay of xylometazoline.